Greek colonization in local contexts - Lucas, Jason; Lucas, Jason; Murray, Carrie Ann; Murray, Carrie Ann; Owen, Sara; Owen, Sara; Millett, Martin; Millett, Martin (University of Cambridge Museum of Classical Archaeology monograph, 2019)
Greek Colonization in Local Context takes a fresh look at Greek colonies around Europe and Black Sea. The emphasis is on cultural interaction, transformation and the repercussions and local reactions to colonization in social, religious and cultural terms. Papers examine the archaeological evidence for cultural interaction in a series of case studies from locations around the Mediterranean and Black Sea regions, at a variety of scales. Contributors consider the effects of colonization on urban life and developments in cities and smaller settlements as well as in the rural landscapes surrounding and supporting them. This collection of new papers by leading scholars reveals fascinating details of the native response to the imposition of Greek rule and the Indigenous input into early state development in the Mediterranean and adjacent regions